GLOBULAR CRYSTALS: RESEARCH REVIEW TO REDEFINING GIANT MOLECULES FOR BIOPHOTONICS APPLICATION IN GREEN ELECTRONICS: Life Sciences-Molecular Biotechnology - MD, SADIQUE SHAIKH (International Journal of Life Science and Pharma Research, 2011)
Chemist and technologist have been dealing for a long time with natural substances consisting long molecules in which the atoms are bound like a links of chain. We find example on every hand: abundant substances as rubber, cellulose, and proteins constitute chain type molecules made up many thousands of atoms. The structural conceptions of such molecules were formed and developed in the twenties, when chemist learned to produce such substances and polymers in their laboratories. Many molecules are capable of winding up into tight coils or, as they are sometimes called, “globules”. Very neat and quite identical globules make up a protein molecule. There is one subtle reason for this. As a matter of fact, a protein molecule contains parts that “like” water, and other parts that have an aversion to water. The parts that do not like water are said to be hydrophobic. The coiling of the protein molecules governed by a single tendency: all the hydrophobic parts are to be hidden inside the globules. This is why the globules in a solution of a protein resemble one another like identical twins. Protein globules are more or less spherical. The size of globules ranges from 100A to 300A, making it readily visible under electron microscope. The first electron micrographs of globular crystals were obtained several decades ago, when electron microscopy techniques were considerably less advanced than they are today. Such a photograph of the tobacco mosaic virus shown in below exhibit.